Grammatical control of sign language production: EMG and motion capture analysis of adjective intensification in Austrian Sign Language (ÖGS) - Krebs, Julia; Harbour, Eric; Malaia, Evie A.; Wilbur, Ronnie B.; Schwameder, Hermann; Roehm, Dietmar (Frontiers in Language Sciences, 2025)
IntroductionThe manuscript presents an experimental investigation into the linguistic and motor control mechanisms underlying grammatical marker production in Austrian Sign Language (ÖGS). It focuses on the cross-linguistically attested phonological parameter of hand articulator tension and its role as a grammatical marker for adjective intensification.MethodBy combining advanced methods, including motion capture and electromyography (EMG), the study allows for a multimodal analysis of grammatical marker production in ÖGS. The experimental data were recorded from six proficient ÖGS signers, each producing fifteen adjectives (based on a set varied in phonological parameters of root forms) in intensified and non-intensified forms. Motion capture data were analyzed in terms of the kinematics of hand and arm movements [velocity, acceleration, as well their temporal distribution such as time to peak deceleration and spatiotemporal index (STI)]; EMG data of muscle activation in forearm and upper-arm flexor and extensor muscles were analyzed both separately and in active combination (using mean and median band-specific EMG and co-contraction indices as measures).ResultsResults revealed significant differences between intensified and non-intensified forms, with intensified adjectives showing higher co-contraction indices in forearm and upper-arm muscles and later deceleration patterns within signs. These findings demonstrate that articulator tension is a quantifiable grammatical marker of intensification, reflected in distinct biomechanical control patterns.DiscussionThis study advances understanding of the neural and motor correlates of sign language production by operationalizing the biophysical basis of grammatical markers. It highlights the linguistic control of biomechanical articulator features, advancing models of language production. Individual variations observed in intensified adjective production suggest further avenues for research into signing styles, language proficiency, and language acquisition. In addition to its linguistic contributions, the manuscript proposes a novel methodological approach for studying variables at the intersection of linguistics, neuroscience, and kinesiology. This work offers practical applications for sign language teaching, language acquisition research, and cross-modal investigations into human language systems, contributing to a broader understanding of linguistic communication as a multimodal phenomenon.